Efficacy and dose-response relationship of oral treprostinil in PAH patients on monotherapy or dual background therapy. (3rd October 2022) - Barbera, J A; Kiely, D; Gruenig, E; Balasubramanian, V; Vizza, C D; Elwing, J; Sood, N; Rao, Y; Holdstock, L; Seaman, S; Broderick, M; White, R J
Abstract: Background: FREEDOM-C and FREEDOM-C2 were randomized, placebo-controlled, double-blinded international, multicenter studies investigating the use of oral treprostinil (TRE) in subjects on mono or dual background pulmonary arterial hypertension (PAH) therapies. Both had a primary endpoint of change in 6-minute walk distance (6MWD) at Week 16 vs baseline. Previous post-hoc analyses combining mono and dual therapy subjects (PDE-5i and/or ERA) from these studies revealed a TRE dose-dependent increase in 6MWD. (1. White & Rao, 2016) Purpose: This post-hoc analysis was performed to determine if subjects from FREEDOM-C and FREEDOM-C2 derive improvements in 6MWD with increasing doses of TRE when stratified by mono or dual background therapy and to determine if PAH background therapies (mono or dual) impacted 6MWD. Methods: All active subjects (n=331) from FREEDOM-C and FREEDOM-C2 were grouped into TRE dose tertiles (low-dose: ≤2 mg BID, mid-dose: >2 mg to ≤3.5 mg BID, and high-dose: >3.5 mg BID). Placebo subjects (n=329) were in a separate 0 mg dose group. No data imputation was implemented. Comparisons of 6MWD change at Weeks 4, 8, 12, and 16 between mono and dual therapy subgroups at any dose group were performed using a two-sample t-test or nonparametric Wilcoxon rank-sum test. The nonparametric Kruskal-Wallis test was conducted with subsequent pairwise comparisons of 6MWD change at Week 16 between the four dose groups through Dunn's approach. Additionally, the Jonckheere-Terpstra test was used to assess the linear trend for 6MWD improvement with higher doses of TRE. Results: Baseline characteristics of the combined intention to treat (ITT) population and summary of 6MWD for subjects with both baseline and Week 16 data are in Table 1. 6MWD change improved steadily to Week 16 in subjects at higher TRE doses, regardless of the number of PAH background therapies (Figure 1). No statistical differences were found between mono and dual therapy at any time point or for any dose group. At Week 16, there was a significant difference in 6MWD change between the placebo group and high dose group within both mono and dual background therapy subjects. The difference between the low- and high-dose groups was significant for subjects on dual background therapy. There was a significant positive linear trend for TRE doses in 6MWD improvement at Week 16 for both monotherapy subjects (one-sided p-value = 0.0002) and dual therapy subjects (one-sided p-value = 0.0242). Conclusions: 6MWD improved in PAH patients regardless of their background therapy (monotherapy or dual background) and derive greater 6MWD improvements with higher doses of TRE. The observed dose-dependent 6MWD increase supports the use of TRE in sequential combination with background therapies (mono or dual). Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): United Therapeutics Corporation